Interaction between humans and computers: key aspects and evolution - Đorđević, Nebojša D.; Đorđević, Veljko N.; Čabarkapa, Obrad T. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The research aimed to analyze the key aspects of human-computer interaction, studying the evolution of this field from its beginnings to contemporary trends. Focusing on different aspects of this interaction, it studied how methods, technologies and principles have evolved over time and shaped our experiences in the digital environment. Methods: The research methodology was based on the analysis of relevant literature and research papers devoted to human-computer interaction. Systematic review and evaluation of sources identified the key information on the evolution of user interaction with computers. Through evaluation of available studies, changes in interface design methods, interaction technologies and understanding of user needs over time were identified. Results: Based on data synthesis, the key aspects of human-computer interaction were identified. An analysis of the literature revealed changes in interface design methods, interaction technologies, and understanding of user needs over time. Specific results included information on the evolution of interaction aspects, including improvements in efficiency, intuitiveness and personalization of experiences. Conclusion: The key conclusion of the research is that innovations and evolution of technology have significantly influenced the way users interact with computer systems. Improvements in interface design, recognition technologies, and personalization of experiences are key factors in creating better user experiences and optimizing human-computer interaction. The research points to the continuous development and changes in the field of human-computer interaction, emphasizing the need for further research and innovation in this area.